Epiphanies of reading: Julia Kristeva's matricide of the native language (Colloquia Comparativa Litterarum, 2025)
This paper is based on a unique teaching experience with young foreign researchers from all geographical and linguistic backgrounds, who were brought together around the texts of French-speaking thinkers, including those of Julia Kristeva, in the "Writing Research in French" workshops that I led at the Cité Internationale Universitaire de Paris. In the light of the concept of symbolic matricide theorised by Julia Kristeva in Melanie Klein: Madness, Matricide as Pain and Creativity (2000), the paper questions the epiphanic moments provoked by the reading of texts in which Kristeva describes the suffering of abandoning her native Bulgarian for an adopted language, inscribing matricide, however painful, at the heart of the experience of rebirth in another language.
Keywords: symbolic matricide; matricide of the native language; destructiveness; ability to think; linguistic exile; poetic experience; epiphany